Comparison of wear resistance of three types of composite resin denture teeth with an acrylic resin denture tooth - Alireza Hashemi Ashtiani; Ali Rohani; Sara Kholghi (Tehran University of Medical Sciences, 2018)
Background and Aims: Wear resistance of artificial teeth has an important role in denture longevity. The purpose of this in vitro study was to evaluate the wear resistance of three types of composite resin denture teeth with that of acrylic resin. Materials and Methods: In this study, four types of artificial teeth, including 3 types of composite artificial teeth (Ivoclar, Apple and Yamahachita) and 1 type of acrylic resin artificial teeth (Ivoclar) were used. Ten maxillary first premolars were selected from each set and were fixed in autopolymerising acrylic resin. The wear test was performed for 1000 and 2000 cycles. The heights and weights were measured under a light stereo microscope and scales (0.001 gram accuracy) before and after wear cycles. Data were analysed by ANOVA and Duncan tests (P=0.05). Results: There was no significant difference between the mean wear of the composite and acrylic resin ivoclar artificial teeth in 1000 and 2000 cycles (P>0.05), but this difference was significant between the other artificial teeth (P<0.05). In 1000 and 2000 cycles, there was a significant difference between the mean weight loss of samples of all four artificial teeth groups (P<0.05). Also, in this study, the composite and acrylic ivoclar artificial teeth showed significantly less wear-resistant than that of other teeth, and the highest wear rate was found for Yamahachita's composite artificial teeth. Conclusion: The findings of this study suggested that Ivoclar composite or acrylic resin denture teeth can be more suitable options than other artificial teeth used in this study in cases susceptible to abrasion.